Checking Out Our Workspaces: An Analysis of Negative Work Environment and Burnout Utilizing the Negative Acts Questionnaire and the Copenhagen Burnout Inventory for Academic Librarians - Albro, Maggie; Stark, Rachel Keiko; Kauffroath, Kelli (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2024)
Objective – This study explored the prevalence of and relationship between bullying and burnout among academic librarians. The authors sought to examine three main factors contributing to negative workplace environment caused by bullying and incivility: (1) the employment characteristics of respondents (i.e., tenured, non-tenure track, and others), (2) librarianship as a second (or third) career, and (3) generational differences.Methods – The researchers administered a survey via professional electronic mailing lists in early spring 2023. Librarians over the age of 18 who hold a Masters of Library Science (MLS) or equivalent degree and were employed in an academic library at the time of taking the survey were eligible to participate. The Negative Acts Questionnaire-Revised (NAQ-R) was used to measure workplace bullying, and the Copenhagen Burnout Inventory (CBI) was used to measure workplace burnout. Survey results were analyzed using RStudio.Results – The responses (n = 267) showed the average bullying score was relatively low (M = 1.57, SD = 0.52), and the average burnout score was middling (M = 45.68, SD = 17.87). The correlation between the two scores was mild (r = 0.5, < 0.001). ANOVAs found no significant difference between NAQ-R scores due to employment type (tenured, non-tenure track, and others; F(6, 260) = 0.711, p = 0.641), duration of employment (F(5, 261) = 0.482, p = 0.79), career number (F(4, 262) = 0.585, p = 0.674), or generational identity (F(5, 261) = 0.0969, p = 0.627). ANOVAs found no significant difference between CBI scores due to employment type (F(6, 260) = 1.566, p = 0.157), duration of employment (F(5, 261) = 1.911, p = 0.0929), career number (F(4, 262) = 1.398, p = 0.235), or generational identity (F(5, 261) = 1.511, p = 0.187).Conclusion – Low to moderate levels of both bullying and burnout were found among academic librarians, but the correlation between the two phenomena was mild. No significant difference was found between employment characteristics, career progression (second or third career), or generational identity and the degree of bullying or burnout experienced. This lack of difference was contrary to researcher predictions and opens the door for further research and understanding of both bullying and burnout among academic librarians.